Anaxibia folia spec. nov.—a new litter-dwelling dictynid spider from India (Araneae: Dictynidae: Dictyninae) - Sankaran, Pradeep M.; Sebastian, Pothalil A. (Zootaxa, 2017)
The dictynid genus Anaxibia Thorell, 1898 currently has six nominal species distributed in the Oriental and Ethiopian regions (World Spider Catalog 2017). The genus represents tiny to small spiders characterised by a reduced cribellum, long, cylindrical anterior and posterior spinnerets, cymbium with caudal modification, palpal patella with dorsal horn, sub-apically arising embolus, conductor with wide lamellar apex and simple female genitalia (Lehtinen 1967). The genus has one representative in India: Anaxibia rebai (Tikader, 1966), originally described under Dictyna Sundevall, 1833 (Tikader 1966; Lehtinen 1967). In this paper, we describe and illustrate a new litter-dwelling Anaxibia species collected from the Kerala state of southern India.